PERENCANAAN SALURAN DRAINASE PADA RUAS JALAN RAYA SERANG - JAKARTA KECAMATAN BALARAJA KABUPATEN TANGERANG - Prayogo, Bhekti Priyo; Yusup, M. Ichwanul; Amilia, Euis (Journal of Sustainable Civil Engineering (JOSCE), 2025)
Roads are one of the most important infrastructures, but in some areas there is often inundation on the road, caused by climate change or land use change. On the Jalan Raya Serang - Jakarta section of Balaraja Subdistrict, Tangerang Regency, flooding often occurs during maximum rainfall intensity, this is because there is no drainage channel that helps water flow to the nearest river. Therefore, research is needed related to drainage planning to prevent flooding. In this study, the rainfall data used is the last 10 years of data, and hydrological analysis using the algebraic average formula, mononabe formula, and gumbel. This study uses a return period with a planned flood discharge obtained for a return period of 5 years = 0.284 m3 / s, a return period of 10 years = 0.329 m3 / s, a return period of 20 years = 0.356 m3 / s, a return period of 50 years = 0.400 m3 / s, and a return period of 100 years 0.442 m3 / s. Two (2) experiments were carried out in the calculation of rainfall data. Conducted 2 (two) experiments in the calculation of channel dimensions. Experiment 1 (one) obtained channel dimensions with channel width (b) 0.70 m, channel height (h) 0.65 m, and can accommodate channel discharge of 1.306 m3 / h. Experiment 2 (two) obtained channel dimensions with a channel width (b) of 0.70 m, channel height (h) 0.50 m, and can accommodate a channel discharge of 0.952 m3 / d.